An analysis of the dress of the female warriors of the palace of Mangkunegara I at the 1991 palace festival - Linda Utami; Sunarmi Sunarmi; Rahayu Adi Prabowo (Pascasarjana Institut Seni Indonesia Surakarta, 2023)
The military apparatus in each region is established to maintain its sovereignty. The Prajurti women of the Mangkunegara Palace were an elite group of soldiers who participated in Raden Mas Said's struggle. As an extraordinary group of warriors in Mangkunegaran history, they have unique clothing that needs further research. The palace attire is one of the important cultural heritages that must be preserved. In Javanese culture, it is taught that dressing appropriately is in accordance with guidelines, situations, and conditions. This article discusses the attire of the Prajurti women of the Mangkunegara Palace, which was reintroduced during the Keraton Festival in 1991 by Trenggono. The research used descriptive analysis techniques, describing the research subject through collected data without analysis or drawing conclusions. The approach used was the aesthetic morphology approach of Thomas Munro. Based on this, this research explains the women's clothing of the Mangkunegara Palace Soldiers by Trenggono, which was displayed at the 1991 Palace Festival. The result shows that there is a discrepancy between the description of the attire of the Prajurti women of the Mangkunegara Palace in Serat Babad Nitik Mangkunegara I and II and the attire created by Trenggono.